Hydrothermal pretreatment for the preparation of wool powders. Issue 8 (22nd November 2013) - Hou, Xiuliang; Xu, Helan; Shi, Zhen; Ge, Mingqiao; Chen, Lifen; Cao, Xiuming; Yang, Yiqi
Abstract Wool powders with low solubility could be easily prepared from wool fibers by combining hydrothermal pretreatment (HTP) and grinding processes. Transforming wool fibers into powders was the first step of exploiting wool as new materials such as bio‐thermoplastics. However, wool fibers were difficult to be prepared into powders only by grinding due to their toughness. This article used a chemical‐free method to obtain wool powders by grinding HTP‐treated wool fibers. Wool fibers after HTP at 130°C for 40 min or above were obviously easier to be broken into snippets with lengths of 25–150 μm after grinding for 1 min and shapeless super‐fine powders with diameters of 3–15 μm after ball milling for 10 min. Wool fibers after HTP were brittle mainly owing to decrease of α‐helices and SS bonds. Combination of HTP and grinding could be an eco‐friendly and feasible treatment to prepare wool powders on industrial scale. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40173.